PENGAMALAN-PENGAMALAN AJARAN AGAMA ISLAM DALAM MEMBENTUK AKHLAK REMAJA MASJID TAWAKAL AIR MELES BAWAH - Wulan Intalia; Yopi Merlina; Yulita Asmara Dewi; Yuni Novia; Siswanto Siswanto (Pendidikan Agama Islam (S2), UNSIQ Wonosobo, Jawa Tengah, 2021)
The background of this research is the practices of Islamic teachings carried out at the Tawakal Air Meles mosque which are actualized through activities carried out by IRMATA, where these activities are expected to shape the morals of the youth of the Tawakal Air Meles Bawah mosque. The purpose of this thesis is to find out how the practices of Islamic religious teachings can shape the morals of mosque youth and the factors that influence the practice of these religious teachings. This study uses qualitative methods with data collection techniques through observation, interviews, and documentation. The research respondents were youth who were active in the mosque, their leaders and their parents. The results of the study show that the practice of Islamic teachings that can shape the morals of youth in the mosque is themselves, such as tadarusan together, mutual cooperation, and commemorating Islamic holidays. The factors that influence the practice of Islamic teachings include the family environment, the mosque environment, and the association of teenagers outside the mosque.